2014
DOI: 10.1016/j.fuel.2014.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach for effective bioethanol production using whole slurry from autohydrolyzed Eucalyptus globulus wood at high-solid loadings

Abstract: h i g h l i g h t sIntegrated process optimization was evaluated for 2G bioethanol production. Enzymatic saccharification of whole-slurry from pretreatment was optimized. Two strategies with/without presaccharification to ethanol production were compared. Optimized conditions lead ethanol titer >6% using industrial yeast strain by SSF. Effective bioethanol production from whole slurry E. globulus was achieved. a b s t r a c tOne of the most important targets and challenges in the second generation bioethanol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 53 publications
1
39
0
1
Order By: Relevance
“…These findings were in agreement with Romaní et al (2014) and Hoyer et al (2009), who reported better performance for SSF than PSSF. The PSSF process significantly increased the % cellulose conversion only when the % cellulose conversion and ethanol concentration were low in the SSF process, but otherwise, it did not have a significant effect, or even had a negative effect when a high cellulose conversion and ethanol content were obtained without a pre-hydrolysis step (Hoyer et al 2013).…”
Section: Pssf Vs Ssfsupporting
confidence: 92%
“…These findings were in agreement with Romaní et al (2014) and Hoyer et al (2009), who reported better performance for SSF than PSSF. The PSSF process significantly increased the % cellulose conversion only when the % cellulose conversion and ethanol concentration were low in the SSF process, but otherwise, it did not have a significant effect, or even had a negative effect when a high cellulose conversion and ethanol content were obtained without a pre-hydrolysis step (Hoyer et al 2013).…”
Section: Pssf Vs Ssfsupporting
confidence: 92%
“…Romaní et al [32] produced cellulosic ethanol from pretreated substrates that were produced by non-isothermal autohydrolysis of E. globulus chips. In this pretreatment procedure, the reactor vessel was heated up to 210 °C and, when this temperature was reached, the heating system was disabled and the reactor was cooled down to ambient temperature for a total pretreatment time of 50 min.…”
Section: Fermentationmentioning
confidence: 99%
“…As for hexane de-oiled olive pomace, the highest reducing sugar concentration was found to be 10.12 g/l obtained with 6 g substrate, Cellic CTec2/Novozyme 188 ratio of 27 for 23 h. Haagensen and coworkers [12] also reported similar reducing sugar concentrations for enzymatic hydrolysis of 100 g/l olive pulp with 100 FPU g −1 (mixture of Celluclast and Novozyme 188) as 10.93 g/l after 7 days of incubation. On the other hand, Sadeghi and coworkes [30] reached 20 g/l sugar concentration after two cycle with 8 h using 100 g substrate per cycle and 40 ml enzyme was loaded which is a significantly high concentration considering the fact that 20% Cellic CTec2/Novozyme 188 ratio used in this study corresponds to 0.1 ml Cellic CTec2 and 0.4 ml of Novozyme 188.…”
Section: Enzymatic Hydrolysismentioning
confidence: 71%
“…The biorefinery approach involves the fractionation of various biomasses from agricultural to marine origins and conversion of each fraction to a value-added product. In the case of lignocellulosic biomasses, alkali, acid and enzymatic hydrolyses along with mechanical pretreatments [12,13] last decades and the fact that biomass supplies roundly 11-14% of total world-wide energy demand [14].…”
Section: Introductionmentioning
confidence: 99%